2016
DOI: 10.1177/1062860615617238
|View full text |Cite
|
Sign up to set email alerts
|

Handoffs in the Intensive Care Unit

Abstract: Operating room (OR) to intensive care unit (ICU) handoffs are complex and known to be associated with adverse events and patient harm. The authors hypothesized that handoff quality diminishes during nights/weekends and that bedside handoff practices are similar between ICUs of the same health system. Bedside OR-to-ICU handoffs were directly observed in 2 surgical ICUs with different patient volumes. Handoff quality measures were compared within the ICUs on weekdays versus nights/weekends as well as between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
6
0
8
Order By: Relevance
“…23,24 We recently evaluated OR-to-ICU handoffs during the weekdays versus nights and weekends using study personnel present within the patient’s room, who evaluated the handoffs in full view of the clinical providers. In that setting, we found significantly better transmitter communication scores on nights and weekends compared with weekdays; however, a Hawthorne effect may have been present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 We recently evaluated OR-to-ICU handoffs during the weekdays versus nights and weekends using study personnel present within the patient’s room, who evaluated the handoffs in full view of the clinical providers. In that setting, we found significantly better transmitter communication scores on nights and weekends compared with weekdays; however, a Hawthorne effect may have been present.…”
Section: Discussionmentioning
confidence: 99%
“…In that setting, we found significantly better transmitter communication scores on nights and weekends compared with weekdays; however, a Hawthorne effect may have been present. 23 The current study may have gauged handoff practices more accurately, as the evaluation was carried out essentially without the transmitters or receivers being aware that they were being evaluated. Another study of change-of- shift handoffs in obstetrical inpatients found that resident handoffs were better in the mornings than evenings, while the opposite was true of the nursing handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…There are more than 20 published studies addressing the transition of patients from the OR to the ICU, with at least 10 published in the last 5 years [15][16][17][18][19][20][21][22][23][24][25]. This particular transition is interesting for multiple reasons.…”
Section: Or-to-icu Handoffsmentioning
confidence: 99%
“…A nursing handover is a vital element in the continuity of care [ 37 ]. Transitions in care are notable periods of vulnerability in a patients’ treatment journey [ 38 ]. Transferring responsibility for a patient’s care to another health care professional increases the chances of an error occurring, especially if key information is communicated inaccurately and inefficiently [ 39 ].…”
Section: Introductionmentioning
confidence: 99%